A Generalized Nonlinear Volterra-Fredholm Type Integral Inequality and Its Application - Limian Zhao; Shanhe Wu; Wu-Sheng Wang (Journal of Applied Mathematics)
We establish a new nonlinear retarded Volterra-Fredholm type integral inequality. The upper bounds of the embedded unknown functions are estimated explicitly by using the theory of inequality and analytic techniques. Moreover, an application of our result to the retarded Volterra-Fredholm integral equations for estimation is given.